1975
DOI: 10.1017/s0043174500062457
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of14C-SAN 6706 in Cotton, Soybean, and Corn

Abstract: The technique of microautoradiography was used to study the localization of14C-SAN 6706 [4-chloro-5-(dimethylamino)-2-(α,α,α-trifluoro-m-tolyl)-3(2H-pyridazinone] in cotton (Gossypium hirsutumL. ‘Coker 203’), soybean [Glycine max(L.) Merr. ‘Lee’], and corn (Zea maysL. ‘W.F. 9’). SAN 6706 was removed from the treatment solutions by absorption and also by adsorption onto the surfaces of roots. Absorbed SAN 6706 appeared to move primarily in the apoplast and to be translocated acropetally and laterally in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Cotton was the only species that recovered from the appli cation of 1.4 kg/ha of norflurazon ( Figure 1) 28 days after emergence. Strang and Rogers (15,16) found that the epi dermis of young cotton roots was an effective barrier to the entrance of a similar herbicide, SAN-6706 in these cells (15,16). They reported that cotton was injured when there was sufficient norflurazon to diffuse into the xylem, move from the transpiration stream into leaf dssue, and saturate the lipids (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton was the only species that recovered from the appli cation of 1.4 kg/ha of norflurazon ( Figure 1) 28 days after emergence. Strang and Rogers (15,16) found that the epi dermis of young cotton roots was an effective barrier to the entrance of a similar herbicide, SAN-6706 in these cells (15,16). They reported that cotton was injured when there was sufficient norflurazon to diffuse into the xylem, move from the transpiration stream into leaf dssue, and saturate the lipids (15).…”
Section: Resultsmentioning
confidence: 99%
“…Other modes of action ascribed to norflurazon are: a) inhibition of the Hill reaction (4), b) alteration of the ratio of linolenic/linoleic acid (4,13,14), and c) influence on the chloroplast ribosomes (4). Lack of translocation and presence of lysigenous or pigment glands are two major factors responsible for its selectivity in cotton (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…For metj1urazone and norjlurazon [30], inhibition of photosynthesis is not relevant during normal agricultural use; these herbicides are applied pre-emergence and give rise to chlorotic seedlings (p. 101), which of course do not possess photosynthetically active chloroplasts. Furthermore, metjlurazone was transported out of the roots only to a very low extent and accumulated in the lysigenous glands of tolerant cotton plants [198,199].…”
Section: H Pyridazinooe Herbicidesmentioning
confidence: 99%
“…Selectivity of norflurazon in the susceptible corn (Zea mays L.) and tolerant cotton (Gossypium hirsutum L.) and soy bean [Glycine max (L.) Merr.] has been reported to be due to differences in absorption and translocation (14,15,16). Similarly, the tolerant species sugarbeet (Beta vulgaris L.) and cranberry (Vaccinium macrocarpon Ait.)…”
Section: Introductionmentioning
confidence: 99%